THE ASPECT OF NEUROCOGNITIVE AND REHABILITATION ON ALEXIA WITHOUT AGRAPHIA CASE - Widyastuti, Ketut; Laksmidewi, Aaa Putri; Widyadharma, Putu Eka (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Alexia without agraphia is a syndrome of disconnection which causes an abruption of visual input to language area. Pure alexia can impact reading ability and create dependency on patients when they do their daily work. An early stage of alexia without agraphia can be detected through a set of neurocognitive evaluation. Besides, it is believed that this assessment has a significant role in anticipating the lag of a proper rehabilitation. Herein, we report a case of a 45-year-old female; she complained about having a visual malaise on her right vision and also said to lose her ability to read very suddenly 14 days prior. On language diagnostic screening, the patient was able to speak fluently, could comprehend and repeated phrases regularly but an experienced loss of color recognition. The patient's visual acuity seemed reasonable and was able to write words or phrases in spite of unable to read. The patient suffered from stage 2 hypertension, hypertriglyceridemia, and diabetes mellitus according to physical examination and laboratory evaluations. Furthermore, an acute infarction on the left posterior cerebral artery which involved the splenium of the corpus callosum and left visual cortex was detected on brain magnetic resonance imaging. Furthermore, the cerebral magnetic resonance angiography results did not show any hemodynamic disruption occurred by occlusion or stenosis. A tactile-kinesthetic exercise and multiple oral re-reading (MOR) program had increased the rehabilitation efficacy for reading ability. However, right-sided homonymous hemianopia did not demonstrate any significant improvements. Alexia without agraphia can be a secondary symptom which occurs in stroke patients, due to the lesion in occipital cortex and area of the posterior corpus callosum on the dominant hemisphere. Neurocognitive evaluation by language diagnostic modalities on alexia without agraphia had demonstrated reading disruption, despite intact writing, and other language-related abilities. Tactile-kinesthetic exercise and MOR were reported to improve the malaise of reading ability.